Tabut in Bengkulu: Comparative Perspectives of KKT and KETAB on Origins, Rituals, and Culturalization - Muhammad Azrul Amirullah; An-nafsi Ma’rifatul Huda (Jurnal Sosiologi Agama, 2025)
The Tabut tradition in Bengkulu is a cultural heritage with strong historical, social, and religious values. This tradition develops in two main groups, namely Kerukunan Keluarga Tabut (KKT) and Kerukunan Tabut Budaya (KETAB). These two groups have differences in the practice and meaning of traditions, so studying from a comparative perspective is interesting. This study aims to analyze the differences and similarities between KKT and KETAB in the implementation of the Tabut Tradition in Bengkulu. This study uses a qualitative method with a comparative study approach. Data was collected through in-depth interviews with KKT and KETAB leaders, direct observation of the implementation of the Tabut Tradition, and related literature studies. Data analysis was carried out using descriptive-analytical techniques to understand the differences and similarities between the two groups. The results of the study show that although KKT emphasizes more religious and ritual aspects in the Tabut Tradition, while KETAB is more oriented towards cultural and tourism aspects, both still play a role in preserving traditions. In addition, it was found that the difference in meaning did not hinder social harmony between the two groups in the implementation of the Ark event every year. The difference in orientation between KKT and KETAB shows the flexibility of the Tabut Tradition in adapting to changing times. Both groups play an important role in preserving this tradition, both in terms of religion.